2014
DOI: 10.1039/c4ra07749k
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic alkanes based high density hydrocarbon fuels preparation and evaluation for LFRJ application

Abstract: Preparation and performance evaluation of high density hydrocarbon fuel for liquid ramjet engine application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…"lignin" and "high Density Biofuel" are more popular in recent years [17][18][19][20][21][22][23][24] .…”
Section: Keyword Analysismentioning
confidence: 99%
“…"lignin" and "high Density Biofuel" are more popular in recent years [17][18][19][20][21][22][23][24] .…”
Section: Keyword Analysismentioning
confidence: 99%
“…Zero‐aromatic, high‐performance jet fuel surrogates prepared from RJ‐4 and various SPKs have recently been studied with RJ‐4 concentrations as high as 50 % [17] . Due to its high density, pure RJ‐4 has applications as a high NHOC fuel for cruise missile propulsion, [38–40] while its low volatility and high flashpoint are well suited for ramjet engines [41] . More recently, researchers have shown that RJ‐4 can be efficiently converted to 1,3‐dimethyladamantane, a thermally stable jet fuel of interest for high speed applications [42] …”
Section: Introductionmentioning
confidence: 99%
“…[17] Due to its high density, pure RJ-4 has applications as a high NHOC fuel for cruise missile propulsion, [38][39][40] while its low volatility and high flashpoint are well suited for ramjet engines. [41] More recently, researchers have shown that RJ-4 can be efficiently converted to 1,3dimethyladamantane, a thermally stable jet fuel of interest for high speed applications. [42] To develop a route to RJ-4 from lignocellulosic feedstocks, it was of interest to explore 2,5-hexanedione [HD (1)] as a platform chemical for the synthesis of methylcyclopentadiene [MCPD (4), Scheme 1].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the densities of cycloalkanes are higher than those of linear hydrocarbons, proving the effects of three-dimensional complex ring structures. Polycyclic hydrocarbon molecules therefore stand out from many molecular types as high energy density molecules …”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic hydrocarbon molecules therefore stand out from many molecular types as high energy density molecules. 15 For the adamantanes, it is a kind of centrally symmetric, highly stable, cagelike hydrocarbon whose basic carbon skeleton structure is very similar to the diamond lattice cell structure. In 1957, Schleyer 16 first synthesized adamantane in the laboratory.…”
Section: Introductionmentioning
confidence: 99%